Números complexos e geometria - Oliveira, Stanley Borges de (2014)
In the presentdissertation we study complex numbers with a special attention to the geometric aspect. Many geometric problems can be answered using the algebraic notation of complex numbers with their rich geometric interpretations with relative ease. The geometric aspects of the complex numbers are often not taught in high school, not even the trigonometric form (or polar form). Therefore, students do not apply the knowledge of complex numbers to solve geometric problems. In this paper we will approach the complex numbers applied to solve both geometric as algebraic problems, making relate geometric concepts with algebraic concepts of complex numbers, and launched as a proposal to develop the ability of students to relate mathematical content offering opportunity of even better ﬁx the concepts of complex numbers.